(untitled) (Applied Biological Research, 2014)
Tenesmus of gastrointestinal origin in dogs is usually accompanied by pain, cramping and involuntary straining efforts. Tenesmus itself is not a disease and is a clinical symptom of colitis, perianal fistulas, colonic and rectal tumours and even of diarrhoea in dogs (Kahn and Line, 2005). This paper reportstenesmus in a non-descript dog due to a penetrating foreign body in rectal mucosa.